The Implementation of Project-Based Learning in Lesson Plan by English Teachers of Senior High Schools in Lembah Gumanti - Annisa Elmida Rizma; Yetti Zainil (Universitas Negeri Padang, 2023)
The purpose of this research is to find out whether teachers are able to write teaching modules based on stages Project- Based Learning. The type of research used in this research was a descriptive. The informants of this research were the English Teachers from 3 senior high schools in Lembah Gumanti. The participants of were 8 English Teachers’. The instruments of this research were a documents analysis and an interview. Based on the documents analysis, can be concluded that of eight informants only the six teachers who have a teaching module, and only three are using a Project-Based Learning module. The result showed that the analysis the teaching module wrote by English teachers found that the teachers have been able to write teaching modules based on Project-Based Learning stages. The stages are written and explained in detail, starting with asking questions, guiding students to design projects, scheduling project completion, monitoring student activity and completion of projects, assessing student projects, and evaluating experiences. The teacher's difficulty in writing a teaching module is to divide every element that exists in the teaching module. In the previous curriculum, there were no elements in the lesson plan, and in the Merdeka Curriculum, each element has already emerged, so it is difficult for the teacher to write it. The teacher says that teaching module is more specific than lessons and does not have the core competence and basic competence of the lesson plan.